Penggunaan Teknik Storytelling dalam Layanan Konseling Anak Usia Dini - Lina Rahma Mustofa; Farach Farida Hady (Child Kingdom : Jurnal Pendidikan Anak Usia Dini, 2025)
This study aims to examine the use of storytelling techniques in guidance and counseling services for early childhood through a library research approach. The background of this study is based on the presence of various socio-emotional problems in early childhood, such as difficulties in emotional regulation, low empathy, and limited social interaction skills. In addition, guidance and counseling services for young children require approaches that align with their developmental characteristics, including the use of concrete and engaging techniques such as storytelling. This research employs a qualitative method with a library research design. Data were collected from various sources, including reputable academic journals, books, and relevant documents. The data were analyzed using content analysis by reviewing, comparing, and synthesizing findings from previous studies. The results indicate that storytelling plays a significant role in supporting children's socio-emotional development, language skills, and self-regulation. Furthermore, storytelling is effective as a therapeutic medium that helps children express their emotions and cope with psychological challenges indirectly. In conclusion, storytelling can serve as a relevant and effective technique in early childhood guidance and counseling services. This study is expected to provide practical insights for educators in developing more appropriate and effective counseling approaches.